Chapter Pyrgi: analysis of possible climatic effects on a coastal archaeological site - Coletta, Virginia (Proceedings e report, 2020)
This work refers to an interdisciplinary study on the archaeological site of Pyrgi, an Etruscan harbour still under excavation, located on the Lazio's coast in Santa Severa, in the province of Rome. The objective of the research is to assess the main cause of the floods and the time the water stays in the site to determine if the floods are periodic phenomena over time or random events for guarantee a correct conservation of the site . The study is based on the combined use of geomatic technologies, meteorological and climatic models, and hydrogeological knowledge.